Measurement of Creative Accounting by Transparency and Disclosure Index (TDI) Method in Automobile Industry - Denich, Ervin; Hajdu, Dániel (Public Finance Quarterly, 2021)
Investigation of relationship between corporate governance and creative accounting came to the front after some accounting scandals (like Enron, WorldCom or Satyam). Corporate governance is an actual topic to discuss due to the its correlation to creative accounting. Application of creative accounting techniques might suggest some weaknesses of a company. In this study we investigate the relationship between corporate governance and creative accounting by applying Transparency and Disclosure Index (TDI) method, which enables to evaluate corporate structure, transparency of operation and disclosure of company related information, based on publicly available data. Then, in order to measure the accounting manipulation, we analyse financial performance measures. Furthermore, we perform a correlation analysis to assess the strength of relationship between corporate governance and creative accounting. As a conclusion, we are able to describe a medium negative correlation between the two aspects under investigation.